2016
DOI: 10.1155/2016/3850402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allicin on Hypertension and Cardiac Function in Chronic Kidney Disease

Abstract: This work was performed to study the effect of allicin on hypertension and cardiac function in a rat model of CKD. The groups were control, CKD (5/6 nephrectomy), and CKD-allicin treated (CKDA) (40 mg/kg day/p.o.). Blood pressure was monitored (weekly/6 weeks). The cardiac function, vascular response to angiotensin II, oxidative stress, and heart morphometric parameters were determined. The CKD group showed hypertension and proteinuria. The coronary perfusion and left ventricular pressures were decreased in CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 42 publications
2
48
0
2
Order By: Relevance
“…This heart-protective effect has also been shown in a rat model of CKD. Protective activity at the kidney level, in addition to the reduction of CKD-mediated systemic hypertension, appears to be due to the antioxidative effect of allicin [167]. In fact, allicin has been shown to improve renal function by modulation of AT1, Nrf2/Keap1 and eNOS pathways.…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…This heart-protective effect has also been shown in a rat model of CKD. Protective activity at the kidney level, in addition to the reduction of CKD-mediated systemic hypertension, appears to be due to the antioxidative effect of allicin [167]. In fact, allicin has been shown to improve renal function by modulation of AT1, Nrf2/Keap1 and eNOS pathways.…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
“…By increasing the nuclear translocation of the Nrf2 factor, allicin also increases the gene transcription of Nrf2-related enzymes, such as CAT, SOD and GPx, which play a key role in the cellular mechanisms defending against oxidative damage. During CKD, allicin has been shown to improve the biochemical markers of renal dysfunction, such as creatinine, blood urea nitrogen, diuresis and proteinuria [167].…”
Section: Plant-derived Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Allicin, the most abundant organosulfur compound in freshly crushed garlic tissues, has been shown to have various health-promoting effects, including anticancer actions [17]. Recent studies suggested that allicin may play a role in CKD, reducing hypertension and oxidative stress, and improving renal dysfunction [18][19][20]. In this study, the effect of allicin on myocardial infarction was evaluated by establishing a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…CKD places the patient into the highest cardiovascular risk level, irrespective of traditional cardiovascular (CV) risk factor stratification. In this regard, we recently reported that allicin treatment in rats with subtotal nephrectomy improves cardiac function and ameliorates oxidative stress and hypertension [ 18 ], supporting the hypothesis that allicin could be important as a complementary and/or alternative therapy to reduce the progression of CKD and decrease the risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 85%